Eur J Rheumatol 2022
DOI: 10.5152/eurjrheum.2021.21022
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression among patients with axial spondyloarthritis

Abstract: Objective: The axial spondyloarthritis (axSpA) mainly affects young population and often leads to reduced mobility, but less is known about the impact it has on mental health. The objective of this study was to determine the prevalence of symptoms of anxiety and depression among axSpA patients and explore the underlying associated factors. Methods: A cross sectional survey-based study was conducted from a single center. A convenient sampling was done to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
10
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 27 publications
6
10
3
Order By: Relevance
“…Previous studies have reported that patients with axSpA had higher levels of depression and anxiety as compared with the general population 53. In our study, 27.4% had possible anxiety (HADS-A≥8), which was lower than previous studies (32%–63%),52 54 55 while 21.2% had possible depression (HADS-D≥8), which was consistent with previous reports (14%–56%) 9 54. Though often comorbid, anxiety often develops prior to depression, and symptoms could have been more reflective of depression at the point of data collection, hence causing the lower prevalence of anxiety 56 57.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have reported that patients with axSpA had higher levels of depression and anxiety as compared with the general population 53. In our study, 27.4% had possible anxiety (HADS-A≥8), which was lower than previous studies (32%–63%),52 54 55 while 21.2% had possible depression (HADS-D≥8), which was consistent with previous reports (14%–56%) 9 54. Though often comorbid, anxiety often develops prior to depression, and symptoms could have been more reflective of depression at the point of data collection, hence causing the lower prevalence of anxiety 56 57.…”
Section: Discussionsupporting
confidence: 90%
“…Inadequate regulation of emotions, known as alexithymia, may predispose individuals to psychological and somatic symptoms 13 . As mentioned above, psychological disorders, such as depression and anxiety, are closely association with alexithymia, 19,22,44 and they are also frequently observed in axSpA patients 10,11 . They can also influence the disease activity and QoL 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, coexisting chronic widespread pain or chronic regional pain that is often linked to impaired quality of life and physical function is not uncommon in axSpA patients 7 . Psychological comorbidities are reported as being closely connected with potentially higher disease activity and poor outcomes in axSpA patients 10–12 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations